Research and application of multi-component sterol determination methods in pre-prepared dishes - Ying, Ying; Hu, Zhengyan; Wu, Pinggu; Luo, Xianfa; Wang, Liyuan; Chen, Jing (Frontiers in Nutrition, 2025)
BackgroundPre-prepared dishes contain fats/oils, high protein, and complex seasonings, making sterol detection difficult due to multiple components and matrix interference. Given the market’s analytical challenges, detecting sterols—key functional components affecting nutritional value—is practically vital. This study aims to develop a sensitive, selective GC–MS method for simultaneous qualitative and quantitative multi-component sterol analysis in pre-prepared dishes and to examine their compositional traits.MethodsAfter saponification treatment, the sample undergoes ultrapure water-assisted dispersion and n-hexane extraction. The extract is dried and subjected to derivatization reaction. The derivative is redissolved and analyzed by gas chromatography–mass spectrometry (GC–MS) for qualitative identification, with quantification performed using the internal standard method. This method optimizes sample pretreatment and chromatographic separation conditions, enhancing detection efficiency and separation effectiveness.ResultsThe six target sterol compounds exhibited good linearity within the concentration range of 1.0–100.0 μg/mL (correlation coefficients ≥0.99). The limits of detection (LODs) and limits of quantification (LOQs) were 0.05–5.0 mg/100 g and 0.165–16.5 mg/100 g, respectively. At low, medium, and high spiked concentrations, the average recoveries ranged from 87.0 to 106%, with relative standard deviations (RSDs, n = 6) of 0.99–9.00%. Application of this method to analyze actual pre-prepared dish samples revealed significant variations in cholesterol content among different dish categories, with meat ingredients playing a dominant role. The sterol composition exhibited marked diversity: ergosterol was not detected in pre-prepared dishes, while β-sitosterol, campesterol, and stigmasterol constituted the major components. Notable differences in sterol content and composition were observed across different categories of pre-prepared dishes, further confirming the impact of various meat raw materials and processing technologies on sterol levels.ConclusionThe GC–MS analytical method established in this study has been validated to demonstrate excellent reliability and applicability, providing an efficient analytical tool for precise detection of multi-component sterols in pre-prepared dishes. This method supports quality control and nutritional value assessment in the pre-prepared dish industry, facilitating product labeling standardization and informed consumer choices.